Wspomnienie Profesora Wiesława Kozuba-Ciembroniewicza - Sondel-Cedarmas, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The paper is devoted to the scholarly work of the late Prof Wiesław Kozub-Ciembroniewicz, a researcher of political and legal doctrines from Kraków. The author examines the most important areas of his research, pointing to Prof Kozub-Ciembroniewicz’s fundamental role in Polish research into the Fascist doctrine. In addition, she stresses Prof Kozub-Ciembroniewicz’s contribution to the analysis of totalitarianism carried out from a broader comparative perspective, not only with regard to Italian Fascism, but also Nazism and Bolshevism.
Keywords: faszyzm; totalitaryzm; doktryny polityczne i prawne; Włochy; Kozub-Ciembroniewicz, Wiesław